2007
DOI: 10.1002/elps.200700118
|View full text |Cite
|
Sign up to set email alerts
|

Detection of novel NF1 mutations and rapid mutation prescreening with Pyrosequencing

Abstract: Neurofibromatosis type 1 (NF1) is caused by mutations in the neurofibromin (NF1) gene. Mutation analysis of NF1 is complicated by its large size, the lack of mutation hotspots, pseudogenes and frequent de novo mutations. Additionally, the search for NF1 mutations on the mRNA level is often hampered by nonsense-mediated mRNA decay (NMD) of the mutant allele. In this study we searched for mutations in a cohort of 38 patients and investigated the relationship between mutation type and allele-specific transcriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 36 publications
(34 reference statements)
3
8
0
Order By: Relevance
“…As has been reported for MSH2 , MLH1 , BRCA1-2 and NF1 7-11, the nuclear scanning NMD model loosely fits with our observations for the APC gene. One of the exceptions is a mutation at intron 14 that creates a skipping of exon 14 and a PTC at the very beginning of exon 15 (data not shown) that associates with imbalanced ASE.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…As has been reported for MSH2 , MLH1 , BRCA1-2 and NF1 7-11, the nuclear scanning NMD model loosely fits with our observations for the APC gene. One of the exceptions is a mutation at intron 14 that creates a skipping of exon 14 and a PTC at the very beginning of exon 15 (data not shown) that associates with imbalanced ASE.…”
Section: Discussionsupporting
confidence: 90%
“…In other cancer predisposition genes such as MSH2 , MLH1 , BRCA1 , BRCA2 and NF1 , studies at the RNA level have shown that mutations causing a premature termination codon (PTC) usually trigger nonsense-mediated decay (NMD) of the mRNA7-11. This mRNA surveillance mechanism reduces the abundance of premature stop-codon-harboring mRNA and of the corresponding truncated proteins.…”
Section: Background and Aimsmentioning
confidence: 99%
“…Additionally, 10 or more NF1 pseudogenes are present in the human genome, and these highly homologous DNA sequences prevent accurate NF1 mutation analysis. Furthermore, at the RNA level, mutation analysis is often hampered by nonsense-mediated mRNA decay (NMD) of the mutant allele [10]. Problems with NMD can be overcome using the protein truncation test (PTT) [11], but the PTT is technically complicated and lacks sufficient sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…Literature search revealed 19 different deep intronic splice mutations reported so far, totally 20 when including the one found in the present study. The results with references are shown in Table 1 [4,16,20,[22][23][24][25][26][27][28][29][30][31][32].…”
Section: Resultsmentioning
confidence: 99%